PENGARUH MONEY ETHICS TERHADAP TAX EVASION DENGAN RELIOGIOUSITY, GENDER, MATERIALISM SEBAGAI VARIABEL MODERATING (Studi Kasus pada Wajib Pajak Orang Pribadi yang Terdaftar di KPP Pratama Malang Utara) - Annisa Zeny Wankhar; Nur Diana (Universitas Islam Malang, 2018)
ABSTRACTThe purpose of this research are: 1) to examine and to know whether there issignificant effect of Money Ethics on Tax Evasion or not. 2) to examine and toknow whether there is significant effect interaction of Money Ethics with IntrinsicReligiousity on Tax Evasion or not. 3) to examine and to know whether there issignificant effect interaction of Money Ethics with Extrinsic Religiousity on TaxEvasion or not. 4) ) to examine and to know whether there is significant effectinteraction of Money Ethics with Gender on Tax Evasion or not. 5) ) to examineand to know whether there is significant effect interaction of Money Ethics withMaterialism on Tax Evasion or not. This Research used primary data as methodto collect the data. Questioneers sheet were distributed to individual tax payer inKPP Pratama Malang Utara.The result shows that there is significant effect of Money Ethics on TaxEvasion. The Interaction of Money Ethics with Religiousity, Gender, andMaterialsm could moderate its relationship with Tax Evasion. On the other hand,Extrinsic Religiousity could not moderate the relationship between Money Ethicsand Tax Evasion.Key word: Money Ethics, Tax Evasion, Intrinsic Religiosity, Extrinsic Religiosity,Gender, dan Materialsm